FUNGAL DISEASE OF VINE AND CHEMICAL AGAINST IT EFFECTIVE WAYS TO FIGHT WITH SUBSTANCES (Journal of Science-Innovative Research in Uzbekistan, 2024)
The article shows the reasons for the development of the Mildew disease, its entry into the cell of the plant through the leaf openings, and the chemical ways of preventing it